2010
DOI: 10.1002/pros.21250
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 25‐hydroxyvitamin D status on serological response to influenza vaccine in prostate cancer patients

Abstract: BACKGROUND Epidemiologic data suggest that there is an association between vitamin D deficiency and influenza infection. We conducted a prospective influenza vaccination study to determine the influence of vitamin D status on serological response to influenza vaccine in prostate cancer (CaP) patients. METHODS During the 2006–2007 influenza season, CaP patients treated at Roswell Park Cancer Institute were offered vaccination with the trivalent influenza vaccine (Fluzone®, 2006–2007) and sera collected for he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
49
2
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 21 publications
1
49
2
1
Order By: Relevance
“…10 virosome adjuvanted TIV in some countries. 13 Consequently, the possible role of VD as a modulator of immune responses to TIV is particularly important in pediatrics.…”
Section: Resultsmentioning
confidence: 99%
“…10 virosome adjuvanted TIV in some countries. 13 Consequently, the possible role of VD as a modulator of immune responses to TIV is particularly important in pediatrics.…”
Section: Resultsmentioning
confidence: 99%
“…51,52 Finally, the strategy of vitamin D supplementation or use as a vaccine adjuvant needs to be explored further, instead of merely optimizing "homeostatic" 25-(OH) D status. [10][11][12][13]26,53,54 Several studies involving mature adult mice that were immunized subcutaneously or intramuscularly with inactivated vaccine (inactivated polio vaccine, 53 Haemophilus influenzae type b oligosaccharide conjugated to diphtheria toxoid vaccine, 54 and hepatitis B surface antigen (HBsAg) 55 ), co-administered with 1,25-(OH) 2 D3 demonstrated production of antigen-specific mucosal immunity (IgA and IgG antibodies), as well as enhanced systemic immune responses. It is likely that vitamin D is not an independent predictor of a binary outcome, but may be influential through its complex immune physiological interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have included subjects already on vitamin D supplementation. [9][10][11][12][13] Epidemiological studies have demonstrated a higher incidence of vitamin D deficiency in elderly and obese populations. 14,15 Recent findings from a longitudinal study of older adults suggest leptin may mediate obesity-related vitamin D deficiency.…”
Section: Introductionmentioning
confidence: 99%
“…As reported in the introduction of our paper, together with the negative results you cited, there are those published by Chadha, et al who demonstrated that a replete VD status is associated with a more frequent response to TIV in prostate cancer patients. 2 Moreover, previous studies enrolled only adults and the different characteristics of children's immune system could have conditioned a different antibody production. Finally, we enrolled otherwise healthy subjects and administered VD day by day for 4 mo after vaccination, whereas in previous studies in two cases immunocompromised patients were included 2,3 and in the third study the active form of VD was given in a single dose at the moment of vaccine injection.…”
mentioning
confidence: 99%
“…2 Moreover, previous studies enrolled only adults and the different characteristics of children's immune system could have conditioned a different antibody production. Finally, we enrolled otherwise healthy subjects and administered VD day by day for 4 mo after vaccination, whereas in previous studies in two cases immunocompromised patients were included 2,3 and in the third study the active form of VD was given in a single dose at the moment of vaccine injection. 4 We think that to definitively establish the real role of VD in conditioning influenza vaccine response in children further studies with different schemes of administration and dosages are needed.…”
mentioning
confidence: 99%